2023
DOI: 10.7717/peerj.15032
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium nitrate and DNA methylation in gastropods: comparison between ovotestis and hepatopancreas

Abstract: Dietary ingestion is the main route of exposure to hazardous contaminants in land animals. Cadmium, a high-profile toxic metal, affects living systems at different organismal levels, including major storage organs (liver, kidneys), key organs for species survival (gonads), and epigenetic networks regulating gene expression. 5-methylcytosine (5mC) is the most common and best-characterized epigenetic mark among different modified nucleosides in DNA. This important player in methylation-driven gene expression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Cadmium induced an increase in the total 5mC content of hepatopancreas DNA, but only for relatively high exposure doses and times (as shown in Table 2). This effect seemed to be mediated by the type of inorganic anion bound to cadmium, with chloride ions having a stronger effect than either sulfate ions or nitrate ions [77][78][79]. The global DNA methylation levels in ovotestis, however, were not affected by exposure to cadmium nitrate [79] (as described in Table 2).…”
Section: Dna Methylation As An Emerging Tool In Ecotoxicologymentioning
confidence: 97%
See 3 more Smart Citations
“…Cadmium induced an increase in the total 5mC content of hepatopancreas DNA, but only for relatively high exposure doses and times (as shown in Table 2). This effect seemed to be mediated by the type of inorganic anion bound to cadmium, with chloride ions having a stronger effect than either sulfate ions or nitrate ions [77][78][79]. The global DNA methylation levels in ovotestis, however, were not affected by exposure to cadmium nitrate [79] (as described in Table 2).…”
Section: Dna Methylation As An Emerging Tool In Ecotoxicologymentioning
confidence: 97%
“…Geyer et al (2016) found that exposure to the demethylating agent 5-aza-C significantly inhibited egg production and embryo development in the planorbid snail, Biomphalaria glabrata [38]. In a study with sexually mature specimens of Cornu aspersum, Drăghici et al (2023) reported significant hypermethylation of the ovotestis compared to the hepatopancreas [79], possibly reflecting the more stringent regulation of genes crucial for reproductive processes in the former organ [83,85]. The foregoing authors also identified significantly elevated transcript levels for several key genes of the DNA methylation machinery in the gonadal structures of B. glabrata compared to somatic tissues, such as the head/foot, central nervous system, buccal mass, salivary glands, hepatopancreas, stomach, heart, kidneys, and mantle edge.…”
Section: Dna Methylation Is An Important Player In Reproduction Growt...mentioning
confidence: 99%
See 2 more Smart Citations
“…Affects the fetus and the central nervous system in Children [230,231], probably carcinogenic to humans [232,233], neurotoxic, nephrotoxic, and hepatotoxic and can also produce effects on the reproductive system, and can also affect fetal development through its passage via the placenta [234][235][236][237][238][239]. Cadmium (Cd) 0.1 ppm -Damage of the kidneys, fragility of the bones, carcinogenic in humans [240][241][242]. Arsenic (As) 0.5 ppm 3 ppm (colorants) Skin eruptions, alopecia, and striation of the nails, but also skin cancer [243], circulatory and peripheral nervous disorders, an increased risk of lung cancer, and a possible increase in the risk of gastrointestinal tract and the urinary system cancers [244].…”
Section: Analysis Of Heavy Metals In Cosmetic Productsmentioning
confidence: 99%